Management Challenge of Culture-Negative Infective Endocarditis in an Adolescent with Uncorrected Patent Ductus Arteriosus: A Case Report - Hermawan, Farhan Aqil Putra; Sari, Linda Silvana; Rahmansyah, M. Badzlul; Prabajati, Anis Wulan (Transpublika Publisher, 2026)
Infective Endocarditis (IE) remains a life-threatening complication for patients with uncorrected Congenital Heart Disease (CHD). This case report illustrates the complex clinical management of a 39 kg pediatric patient presenting with a five-day history of fever and acute heart failure. Clinical examination and Transthoracic Echocardiography (TTE) confirmed the presence of a Patent Ductus Arteriosus (PDA) with associated bacterial vegetation, consistent with IE. The patient’s condition was further complicated by sepsis and hypochromic microcytic anemia. Management required a high-precision, multi-modal approach to balance competing physiological demands. To eradicate the infection, a synergistic regimen of broad-spectrum antibiotics (Ceftriaxone and Gentamicin) was initiated. Simultaneously, heart failure was addressed using a combination of diuretics (Furosemide, Spironolactone) and afterload reduction via ACE-inhibitors (Captopril). A critical component of the intervention was strict fluid restriction (1900 ml/day) to prevent pulmonary volume overload, despite the concurrent systemic sepsis. Supportive therapies included corticosteroids and gastrointestinal care. This case demonstrates that while sepsis typically necessitates fluid resuscitation, the presence of a PDA-induced shunt requires cautious fluid titration to maintain hemodynamic stability. The successful stabilization of this patient underscores the necessity of aggressive antimicrobial therapy and meticulous fluid management in complex CHD complications. Ultimately, this report emphasizes the vital importance of early PDA closure as a primary preventive measure against the development of high-morbidity Infective Endocarditis.